Digital Transformation and Firm Performance: The Moderating Role of CFO co-optation - Rudyanto, Astrid; Carolina, Vonny; Firnanti, Friska; Djashan, Indra Arifin (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Abstract Purpose: This study tests whether digital transformation affects firm accounting performance in Indonesian manufacturing firms, and whether CFO co-optation moderates that effect. Research Methodology: The study draws a panel of 285 firm-year observations from 95 manufacturing firms listed on the Indonesia Stock Exchange between 2022 and 2024, sourced from audited annual reports and financial statements. The study measures digital transformation through text-mining keyword frequency in annual reports and codes CFO co-optation as a binary indicator for CFO appointment during the sitting CEO's tenure. The study estimates a Fixed Effects panel regression in Stata 17, selected through Chow and Hausman tests, with Moderated Multiple Regression testing the interaction effect. Results: Digital transformation lowers Return on Assets at the 10% significance level. CFO co-optation lowers ROA at the 5% level, but the interaction between digital transformation and CFO co-optation raises ROA at the 5% level, offsetting and reversing the direct penalty. Conclusions: Executive alignment through CFO co-optation buffers the short-term cost digital transformation imposes on profitability, consistent with Resource Orchestration Theory operating alongside Agency Theory rather than replacing it. Limitations: The sample covers manufacturing firms only, over a three-year window, using a keyword-based digital transformation proxy. Contributions: The findings extend Agency Theory and Resource Orchestration Theory into a joint governance-technology model and offer Indonesian regulators, boards, and CFOs concrete guidance on staffing and timing digital transformation initiatives.